KEKELIRUAN DALAM MENYELESAIKAN SOAL OPERASI HITUNG PENGURANGAN PADA PESERTA DIDIK DI SEKOLAH DASAR PENYELENGGARA PENDIDIKAN INKLUSIF KECAMATAN PAUH KOTA PADANG - Zesti; zelin (Universitas Negeri Padang, 2015)
Zesti and Zelin. 2015. The Students’ Mistakes in Solving Subtraction Items in Elementary School Students in Inclusive Education in the District Organizer of Padang Pauh. Thesis. Graduate Program of State University of Padang. This research was conducted due to the mistakes done by the students in solving row-down subtraction items by using saving technique in Elementary School Students in Inclusive Education in the District Organizer of Padang Pauh. The aim of this research was describe the students’ mistakes in solving row-down subtraction items by using saving technique. This research applied descriptive quantitative method. The data were gathered by administering a written test to the students having problems with completing the subtraction items. The result of data analysis indicated that the students’ mistake in recognizing symbol was 11,61% (very small), the students’ mistake in recognizing place was 35,95% (very small), the students’ mistake in the process of saving was 65,51% (big), the students’ mistake in calculating was 11,83% (very small), and the students’ mistake in writing was 3,38% (very small). Based on these results, it was concluded that in completing solving row-down subtraction items, the mistake was frequently occurred in the process of saving the numbers in which the students did not save the numbers but directly subtract them.1Zesti And Zelin(1), Mahasiswa Jurusan Pendidikan Luar Biasa,FIP,UNP.2Elsa Efrina(2), Dosen Jurusan Pendidikan Luar Biasa,FIP,UNP.3Zulmiyetri(3), Dosen Jurusan Pendidikan Luar Biasa,FIP,UNP.